2021
DOI: 10.1039/d1sm00221j
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes hosted in redox-active ionically cross-linked polyelectrolyte networks enable more efficient biofuel cells

Abstract: Self-assembled nanobiocatalyst. Phosphate-mediated cross-linking of redox polyelectrolytes and glucose oxidase leads to self-assembled nanostructures with higher output power density per mol of mediator, thus enabling more efficient biofuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…The quartz crystal microbalance with dissipation (QCM-D) experiments were performed, using redox polyelectrolyte and enzyme solutions as described for graphite electrode modification, following a procedure previously reported. 21 IR Spectroscopy. Polarization modulation infrared reflection absorption spectroscopy (PM-IRRAS) experiments were performed following a procedure previously reported.…”
Section: ■ Materials and Methodsmentioning
confidence: 74%
See 4 more Smart Citations
“…The quartz crystal microbalance with dissipation (QCM-D) experiments were performed, using redox polyelectrolyte and enzyme solutions as described for graphite electrode modification, following a procedure previously reported. 21 IR Spectroscopy. Polarization modulation infrared reflection absorption spectroscopy (PM-IRRAS) experiments were performed following a procedure previously reported.…”
Section: ■ Materials and Methodsmentioning
confidence: 74%
“…The complex [Os(bpy) 2 Cl-(PyCHO)]Cl was synthesized as previously reported by Kober et al 20 The osmium-modified branched PEI (OsPEI) was synthesized as previously reported. 21 The osmium-modified PAA (OsPAA) was synthesized by adapting the procedure reported by Hermanson. 22 1 mg/mL PAA and 4.6 mM osmium complex in 0.2 M carbonate/ bicarbonate buffer solutions at pH 9.6 were prepared.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations